Preparing for the youth basketball European Championship: Perceptual response and acute effects of an injury prevention program - Arede, J.; Ferreira, A. P.; Esteves, P.; Gonzalo-Skok, O.; Leite, N. (International Journal of Sports Science & Coaching, 2022)
The aims of this study were to determine the feasibility of the injury prevention program (IPP), to examine the reliability of perceptual response to an IPP and to analyze the acute effects of both external and internal demands of in-court training sessions in the IPP. Twelve young basketball players participated in a national team (NT) training camp (120 total individual samples). While players only completed five exclusive in-court training sessions, the IPP was always performed before such in-court practices in the rest of the sessions. The rating of perceived exertion (RPE) was determined at the completion of each IPP. Training load (TL) measures during in-court practices were collected using indoor tracking system, and individual heart rate monitors. Independent t-tests and analysis of variance were used to compare between-sessions TL measures and to test the main effect of RPE in TL. The mean RPE of all IPP sessions was 14.7 ± 0.86. Moreover, there was moderate reliability (ICC = 0.69) between IPP sessions for the RPE and an acceptable coefficient of variation (CV = 4.45%). Furthermore, after IPP, subjects significantly covered more distance per minute (total, = 6 km/h and 6.1-12 km/h) and performed a higher number of body impacts per minute (total, very light and moderate do heavy). Also, the main effect of RPE during IPP sessions was significantly observed in distance covered per minute (total and 12.1-18 km/h) during in-court training sessions. This IPP could serve as a feasible and reliable strategy to implement during NT preparation.